2019
DOI: 10.1101/636712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LIR-dependent LMX1A/LMX1B autophagy crosstalk shapes human midbrain dopaminergic neuronal resilience

Abstract: The LIM homeodomain transcription factors LMX1A and LMX1B are essential mediators of midbrain dopaminergic neuronal (mDAN) differentiation and survival. Here we show that LMX1A and LMX1B are autophagy transcription factors in iPSC-derived human mDANs, each contributing to the expression of important autophagy genes including ULK1, ATG7, ATG16L1 and TFEB. Suppression of LMX1A and LMX1B in mDANs reduces basal autophagy, lowers mitochondrial respiration, and elevates mitochondrial ROS levels; meanwhile overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Although initially proposed as a nuclear-cytoplasmic shuttle responsible for removing proteins from the nucleus, recent reports have suggested a broader functional repertoire [21,25]. ATG8 has been identi ed as a transcriptional cofactor that participates in the regulation of gene expression together with transcriptional regulators [23,24]. In particular, in plants, MeWRKY and MeATG8 interact to activate PR gene transcription [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially proposed as a nuclear-cytoplasmic shuttle responsible for removing proteins from the nucleus, recent reports have suggested a broader functional repertoire [21,25]. ATG8 has been identi ed as a transcriptional cofactor that participates in the regulation of gene expression together with transcriptional regulators [23,24]. In particular, in plants, MeWRKY and MeATG8 interact to activate PR gene transcription [26].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, under the absence of stress conditions, some autophagic bodies were observed. StATG8 interacts with the transcription factor WRKY Previous studies have shown that WRKY, a transcriptional regulator, interacts with ATG8, and it has recently been reported that human LC3B interacts with the transcription factor LMX1B and acts as a transcriptional cofactor [23,24]. Based on this, putative candidates with AIM among Arabidopsis transcription factors were analyzed in the iLIR Autophagy Database.…”
Section: Statg8 Forms Homodimersmentioning
confidence: 99%
See 1 more Smart Citation
“…In post-mitotic mDAn, Lmx1a/b directly regulates the expression of the dopamine transporter (DAT) and the vesicular monoamine transporter 2 (Vmat2), genes necessary for mDAn terminal differentiation and markers of mature mDAn [15][16][17]. According to recent findings, Lmx1a/b expression is also maintained throughout adulthood, and, by regulating autophagy and mitochondrial metabolism, provides protection against cellular stress [18,19]. For all these reasons, Lmx1a is effectively used in combination with other TFs to improve DA differentiation in vitro and in vivo from different cellular systems [15,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%